The Muslim Religiosity-Personality Measurement Inventory (MRPI)'s religiosity measurement model: towards filling the gaps in religiosity research on Muslims - Krauss, Steven Eric; Hamzah, Azimi; Suandi, Turiman; Mohd Noah, Sidek; Mastor, Khairul Anwar; Juhari, Rumaya; Kassan, Hasnan; Mahmoud, Azma; Manap, Jamiah (Universiti Putra Malaysia Press, 2005)
Since the advent of religiosity as a field of scientific inquiry, it has been under the domain of psychologists of religion. The approach taken toward conceptualizing religiosity, therefore, has always been one purported to be of religious universalism. However, the overwhelming majority of religiosity instruments to date have fallen under the rubric of Christianity and the study of Christian people. As the desire to learn more about the religious life of the non-Christian traditions and people spreads, there is an increasing need for religiosity concepts and instruments to reflect these particular religious traditions. The role of religious worldview, therefore, is a major consideration in the instrumentation of religiosity, as worldview provides an underlying philosophical foundation for the operationalization of religiosity concepts, constructs and items. As the preponderance of religiosity instrumentation to date has been grounded in the Judeo-Christian religious worldview, existing religiosity instrumentation is also reflective of it, and as such, does not adequately represent the uniqueness of other non-Judeo-Christian worldviews such as the Islamic tawhidic worldview. As such, the Current study aimed to provide a general overview of religiosity conceptualization in general, along with some of the major gaps in religiosity research for Muslims. In response, the paper concludes with the presentation of a basic religiosity model rooted in the tawhidic worldview of Islam, upon which the Muslim Religiosity-Personality Inventory (MRPI) was based.